The scientific impact of Danish research 1980-2020 - Schneider, Jesper Wiborg; Norn, Maria-Theresa (CFA Scientific Reports, 2023)
In 2012, Gunnar Öquist and Mats Benner published a report that drew attention to an impressive increase over the period 1990 to 2010 in the mean citation impact of Danish research and in its proportion of highly cited papers. The development in Danish research impact during the period was so exceptional that it was referred to it as a "Danish miracle". The aim of this study is to update and extend the bibliometric analyses presented in Öquist and Benner’s report to examine the development since 2009 in the relative citation impact for publications affiliated to Denmark. We document that there has been a continuous decline since 2010 in the relative citation impact of publications with Danish affiliations. Similar declines are observed in several other countries with which Denmark is often compared, but the Danish decline sets in earlier and appears more pronounced. The decline appears across major scientific fields and universities, with minor variations and a few exceptions. Around 2010, Denmark belonged to a small group of countries with the highest relative citation impact. Today, Denmark belongs to a much larger group of countries with a lower albeit above-average citation impact.